International Criminal Court and Nigeria : implementing the complementarity principle of the Rome Statute - Adigun, Muyiwa (New York, NY : Routledge, 2018)
"If Nigeria fails to prosecute the crimes recognised under the Rome Statute, then the International Criminal Court (ICC) will intervene. The ICC is only expected to complement the criminal justice system in Nigeria and is not a court of first instance, but one of last resort. This is what is known as the principle of complementarity. Before the ICC can step in, it must make a finding of 'unwillingness' or 'inability' on the part of Nigeria. It is only after this finding is made that the ICC can take over the prosecution of the crimes recognised under the Statute from Nigeria. This book examines the criminal justice process in Nigeria and discovers that the justice system is latent with the requirements of 'unwillingness' and 'inability.' The requirements, which serve as tests for assessment, are as they are laid down by the Rome Statute and interpreted by the ICC. This book offers recommendations as to what Nigeria must do in order to avoid the ICC intervention by reversing those parameters that give rise to 'unwillingness' and 'inability.' [This book] offers a contribution to the advancement of international law and will be of practical use to African countries. It aims to sensitise policy makers in different African countries in respect of policy options open to them to close impunity gap in their respective countries."--
Introduction -- The Nigerian legal system and the implementation of the Rome Statute complementarity principle -- Complementarity under the Rome Statute of the International Criminal Court -- Inaction : adoption of implementing legislation as an aspect of complementarity -- Unwillingness : shielding from criminal responsibility I -- Unwillingness : shielding from criminal responsibility II -- Unwillingness : independence and impartiality of the prosecuting authority and the judiciary -- Inability : the need for witness protection, extradition arrangement and delegation of criminal jurisdiction to other states -- Conclusion and recommendations.
Based on the author's thesis (doctoral - University of the Witwatersrand, Johannesburg, 2015) issued under title: Implementing the complementarity principle of the Rome Statute of the International Criminal Court in Nigeria.
Includes bibliographical references and index.
Keywords: Rome Statute of the International Criminal Court -- (1998 July 17); Rome Statute of the International Criminal Court (1998 July 17); International crimes -- Nigeria; Impunity -- Nigeria; Complementarity (International law); Complementarity (International law); Impunity; International crimes; Nigeria; International Criminal Court; Rome Statute (Rome, 17 July 1998).; International crimes; Complementary jurisdiction; International law and national law; Nigeria